Bacteriophage Cocktail for the Prevention of Multiple-Antibiotic-Resistant and Mono-Phage-Resistant Vibrio coralliilyticus Infection in Pacific Oyster (Crassostrea gigas) Larvae - Hyoun Joong Kim; Jin Woo Jun; Sib Sankar Giri; Sang Guen Kim; Sang Wha Kim; Jun Kwon; Sung Bin Lee; Cheng Chi; Se Chang Park (Pathogens, 2020)
Vibrio coralliilyticus (V. coralliilyticus) is a pathogen that causes mass mortality in marine bivalve hatcheries worldwide. In this study, we used a bacteriophage (phage) cocktail to prevent multiple-antibiotic-resistant (MAR) and phage-resistant (PR) V. coralliilyticus infection in Pacific oyster (Crassostreagigas) larvae. To prevent the occurrence of phage-resistant strains and decrease the effect of mono-phage treatment, we prepared a phage cocktail containing three types of V. coralliilyticus-specific phages and tested its prophylactic efficacy against MAR and PR V. coralliilyticus infection. The results of the cell lysis test showed that the phage cocktail showed an excellent bactericidal effect against the MAR and PR variants in contrast to the experimental group treated with two mono phages (pVco-5 and pVco-7). An in vivo test using Pacific oyster larvae also confirmed the preventive effect against MAR and PR variants. In conclusion, the application of the phage cocktail effectively prevented V. coralliilyticus infection in marine bivalve seedling production. Furthermore, it is expected to reduce damage to the aquaculture industry caused by the occurrence of MAR and PR V. coralliilyticus. Therefore, phage cocktails may be used for the control of various bacterial diseases.